“STUCK IN THE MIDDLE OF NOWHERE?“ DECONSTRUCTION AND RECONSTRUCTION OF IDENTITIES AMONG 1.5 GENERATION AFRICAN IMMIGRANT YOUTH IN NORTH AMERICAN SOCIETIES: DILEMMAS AND CHALLENGES - Buster, C. Ogbuagu; Baffoe, Michael (European Scientific Journal, ESJ, 2015)
The migration and resettlement of people into new societies have created a host of problems for immigrants in host societies. The migration and settlement experiences are more complicated and challenging for the immigrant youth who arrive in the new societies in their teenage years. This group, now referred to as the one-and-a-half generation group in the Diaspora, straddle various worlds: those of the old home they migrated from, and those of the new Diasporic settings, but not fully belonging to any. For these teenage youth growing up in Diasporic settings, the issue of identity becomes more paramount. How they come to define themselves, as well as how others define them, have important implications for their successful integration or the lack thereof in new societies. This study, undertaken with a number of youth from Africa, who have migrated, mostly with their families, into North America, unearthed some pertinent issues surrounding identity deconstruction and reconstruction in new societies for migrant youth.